Bifunctional N-doped hierarchical porous carbon nanosheets derived from heterologously-expressed spidroin for supercapacitors and oxygen reduction reaction. (August 2022) - Kang, Zepeng; Pang, Zhao; Zi, Zhenzhen; Liu, Bin; Zhai, Huanhuan; Bai, Yu; Zhu, Zhiguang
Abstract: Herein, a novel hierarchical porous carbon nanosheet with high N content was successfully prepared by pyrolyzing a spidroin heterologously expressed in engineered Escherichia coli through a pre-carbonization process and a subsequent KOH activation process. The as-obtained carbon materials absolutely inherited the characteristics of natural spidroin at the molecular level and presented a nanosheet structure. At an activation temperature of 800 °C, the material exhibited a large specific surface area (2170 m 2 g −1 ) and a high N content (2.83 wt%). As a result, this material (AS-PC800 ) displayed a specific capacitance ( C g ) of 561 or 384 F g −1 at 0.5 A g −1 in 6 M KOH electrolyte, based on a three- or two-electrode system, respectively. The assembled symmetrical coin-like supercapacitor showed a good rate capability ( C g held 353 F g −1 at 20 A g −1 ) and cycling stability ( C g retained over 95.8% after 10000 cycles at 5 A g −1 ). The symmetrical device delivered a high energy density of 85.84 Wh kg −1 at a power density of 800 W kg −1 with the [BMIm]BF4 /AN electrolyte. Additionally, AS-PC800 exhibited the optimal oxygen reduction properties. The onset reduction potential began at 0.98 V vs. RHE which is very close to that of the commercial 20% Pt/C (1.04 V) catalyst. This work provides an innovative method for exploring novel biomass precursors in the development of porous carbon materials for energy conversion and storage applications. Graphical abstract: Image 1 Highlights: A new carbon nanosheet derived from a native-sized recombinant spidroin is prepared. This carbon nanosheet inherits the trait of the spidroin at the molecular level. The carbon nanosheet exhibits excellent supercapacitance and ORR property. This work uses the synthetic biology means to explore new carbon materials.